Effects of spalling fault on dynamic responses of gear system considering three-dimensional line contact elasto-hydrodynamic lubrication. (February 2022) - Wang, Liming; Deng, Chunlong; Xu, Jin; Yin, Lei; Yu, Wennian; Ding, Xiaoxi; Shao, Yimin; Huang, Wenbin; Yang, Xiaoqing
Highlights: A dynamic model with spalling fault considering 3D line contact EHL is established. Meshing stiffness and dynamic responses are obtained considering the effects of spalling and lubrication film. Meshing force over the oil film is calculated iteratively instead of a given quasi-static meshing force. Abstract: Spalling is a common fault in gear system, which directly degrades the performance of the gear system and increases the risk of downtime of the entire system. Until now, lots of efforts have been done to study the underlying mechanism of the spalling fault and its effects on dynamic characteristics for the purpose of accurate diagnosis. However, the lubrication characteristics affected by the spalling fault are usually neglected, which degrades the modelling accuracy of gear system with spalling fault. Therefore, a new dynamic modelling method with spalling fault considering three-dimensional (3D) line contact elasto-hydrodynamic lubrication (EHL) is proposed in this paper. With the established model, the contact characteristics of the lubrication film between gear teeth affected by the spalling fault and the dynamic responses of the gear system can be studied. The main differences of the proposed model are that the meshing force over the lubrication film is calculated iteratively instead of a given quasi-static meshing force and the comprehensive meshing stiffness is obtained considering the effects of both spalling fault and lubrication film. The effects of spalling fault on film pressure distribution, film thickness distribution, film stiffness, comprehensive meshing stiffness and dynamic responses are studied based on the proposed method. Finally, the proposed 3D line contact EHL model is verified by comparing to a traditional EHL model. Effects of the spalling fault size on the comprehensive meshing stiffness and the dynamic responses of the gear system are investigated and discussed. The results reveal that this work can provide a more reasonable analytical method for understanding the contact characteristics and dynamic responses of gear system with spalling fault.